Growth and immune response of Litopenaeus vannamei fed on β-(1, 3) glucan and poly-β hydroxybutyrate - Sarmin, ,; Suprayudi, Muhammad Agus; Jusadi, Dedi; Ekasari, Julie (Jurnal Akuakultur Indonesia, 2013)
ABSTRACT This research was aimed to examine the growth performance and non-specific immune response of Pacific white shrimp (Litopenaeus vannamei) fed on the diet supplemented with β-(1,3) glucan (BG) and poly-β-hydroxybutyrate (PHB) as feed additives. Shrimp juvenile at an initial body weight of 2.06±0.03 g was randomly distributed into 12 units of aquaria at a density of 20 shrimps/tank and reared for 42 days. The treatments applied in this study were control (without feed additives), 1.5 g/kg BG, 10 g/kg PHB and 1,5 g/kg BG+10 g/kg PHB. Results showed that shrimp fed on 1.5 /kg BG-supplemented feed had significantly higher growth performance and non-specific immune response. Keywords: growth, shrimp, non-specific immune response, Litopenaeus vannamei  ABSTRAK Penelitian ini bertujuan untuk menguji kinerja pertumbuhan dan respons imun nonspesifik udang vaname Litopenaeus vannamei yang diberi pakan dengan penambahan feed additive berupa β-(1,3) glukan (BG) dan poli-β-hidroksibutirat (PHB). Juvenil udang 2,06±0,03 g dipelihara pada 12 unit akuarium dengan empat perlakuan dan tiga ulangan, serta padat tebar 20 ekor/tank selama 42 hari pemeliharaan. Perlakuan yang diberikan dalam penelitian ini yaitu penambahan BG (1,5 g/kg), PHB (10 g/kg), dan BG (1,5 g/kg)+PHB (10 g/kg), serta kontrol (tanpa penambahan feed additive). Hasil penelitian menunjukkan bahwa udang yang diberi 1,5 g/kg BG memiliki kinerja pertumbuhan dan respons imun nonspesifik yang terbaik. Kata kunci: pertumbuhan, udang, respons imun nonspesifik, Litopenaeus vannamei